Fear of COVID-19 and Life Satisfaction: The Role of the Health-Related Hardiness and Sense of Coherence - Dymecka, Joanna; Gerymski, Rafał; Machnik-Czerwik, Anna; Derbis, Romuald; Bidzan, Mariola (Frontiers in Psychiatry, 2021)
Introduction: The COVID-19 pandemic is contributing to increased fear and anxiety throughout society, which may affect life satisfaction. Health-related hardiness and sense of coherence are personal resources that help people adapt to difficult circumstances. The purpose of this study was to investigate the relationship between fear of COVID-19, sense of coherence, health-related hardiness, and life satisfaction. Methods: A total of 907 Polish people (522 women and 385 men) participated in this study. The Fear of COVID-19 Scale (FOC-6), the Health-Related Hardiness Scale, the Sense of Coherence Scale (SOC-29), and the Satisfaction with Life Scale were used. Results: Correlation showed that fear of COVID-19 was negatively related to health-related hardiness, sense of coherence, and life satisfaction. Health-related hardiness and sense of coherence were positively related to life satisfaction. Both sense of coherence and hardiness were mediators between fear of COVID-19 and life satisfaction during the current pandemic. Conclusion: Sense of coherence and health-related hardiness are personal resources that are important for dealing with the effects of the COVID-19 pandemic. According to our study, sense of coherence and hardiness can mediate between fear of COVID-19 and life satisfaction. Presented cross-sectional results have to be verified in future longitudinal studies in order to strengthen the conclusions presented in this manuscript. This study verified the role of only two personal resources, so more research is needed on the role of other personal resources during COVID-19 pandemic.